Planning Majelis Taklim Ibu-Ibu Al - Haura Kisaran Dalam Mensosialisasikan Bahaya Penggunaan Gadget Bagi Anak - Siregar, Eni Dayati; Saburi, Annai (Universitas Cokroaminoto Yogyakarta, 2025)
The Al-Haura Range Mothers' Taklim Council designed an outreach program to raise parents' understanding of the dangers of using gadgets for children. As The aim of this research is to ascertain the planning of the Al-Haura Kisaran mothers taklim assembly in socializing the dangers of gadget use for children and to review the extent of success of a plan carried out by the mothers of the Al-Haura Kisaran mothers in socializing the dangers of gadget use for children. Field research using a qualitative approach is the research methodology employed, with the goal of analyzing the planning of the Al-Haura Kisaran mothers taklim assembly in socializing the dangers of gadget use for children and includes findings and interviews to obtain a thorough comprehension of the planning executed by the Al-Haura mothers in socializing the dangers of gadget use for children. The results of this study are that the mothers of the Al-Haura Kisaran mothers taklim assembly have succeeded in planning about the dangers of gadgets for children carried out by the mothers of the Al-Haura Kisaran mothers taklim assembly.